1994
DOI: 10.1073/pnas.91.7.2415
|View full text |Cite
|
Sign up to set email alerts
|

Impact of malaria on genetic polymorphism and genetic diseases in Africans and African Americans.

Abstract: The high mortality from malaria in sub-Sahara Africa selected multiple genes that give the population a selective advantage. Identification of the genetic basis for resistance may suggest unusual approaches to development of malarial vaccines and antimalarial drugs. Some of these genes may be deleterious, although of selective advantage within the African setting, and need to be identified for counseling for disease prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
61
0
5

Year Published

1997
1997
2006
2006

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 108 publications
(68 citation statements)
references
References 43 publications
2
61
0
5
Order By: Relevance
“…The Fy(a−b−) phenotype occurs in 60% of AfricanAmericans but 100% of West African populations; red cells with this type are unable to be invaded by Plasmodium vivax. 23 The CR1 protein appears to play a major role in the rosetting of Plasmodium falciparum infected red cells to uninfected cells. This phenomenon has been correlated with the increased severity and mortality of falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The Fy(a−b−) phenotype occurs in 60% of AfricanAmericans but 100% of West African populations; red cells with this type are unable to be invaded by Plasmodium vivax. 23 The CR1 protein appears to play a major role in the rosetting of Plasmodium falciparum infected red cells to uninfected cells. This phenomenon has been correlated with the increased severity and mortality of falciparum malaria.…”
Section: Discussionmentioning
confidence: 99%
“…1 A better knowledge of the polymorphic host genes associated with resistance to clinical malaria and/or with high parasite densities might provide new insights into disease mechanisms, and suggest new approaches for prophylactic or therapeutic interventions. 2 Although several host genetic factors related to resistance to severe malaria (cerebral malaria, severe anemia) have convincingly been listed, 3 the same is not the case for the mild expression of the disease. 4 Indeed, concerning red blood cell polymorphisms for example, no study has revealed any influence of ABO blood groups on the susceptibility to mild malaria 5 nor on the delay of reinfection after curative anti-malarial treatment.…”
Section: Introductionmentioning
confidence: 99%
“…comm.). It is also possible that differences in the Na/K composition of red cells between races may have resulted from exposure to malaria in the past, although so far the molecular basis for this phenomenon has not been investigated (Miller 1994).…”
Section: Malariamentioning
confidence: 99%
“…The protective effect of a deficiency of the red cell enzyme, glucose-6-phosphate dehydrogenase (G6PD), has been confirmed recently by Ruwende et al (1995), who have found that both female heterozygotes and male hemizygotes have a reduced risk, ∼50%, of having severe malaria. Protection is also mediated by variation in the structure or synthesis of a variety of red cell-surface antigens (Miller 1994); the molecular basis for the absence of the Duffy antigen, found many years ago to be associated with resistance to P. vivax malaria, has now been defined as a substitution in the binding site for the GATA 1 erythroid transcription factor at position ‫64מ‬ to the promoter (Tournamille et al 1995). By gene mapping analysis for the Melanesian form of ovalocytosis, which is sometimes difficult to identify phenotypically, it has been found that this polymorphism provides complete protection against cerebral malaria (S. Allen, pers.…”
Section: Malariamentioning
confidence: 99%